A Representasi Kemiskinan Absolut Tokoh Utama Dalam Novel La Muli Karya Nunuk Y Kusmiana - Talitha Lulu Kharisma; Sugiarti Sugiarti (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2022)
This study aims to show the form of absolute poverty of the main character in the novel La Muli by Nunuk Y Kusmiana. In this study, the concept of poverty is used to analyze the forms of absolute poverty. The approach in this research is the sociology of literature which focuses on the reflection of the problems of social life in the novel La Muli. This research is included in the type of qualitative research with a descriptive form. Data collection techniques using reading and note-taking techniques. The reading and note-taking technique was carried out by reading the novel La Muli by Nunuk Y Kusmiana repeatedly to track events that occurred as research data and used for analysis. The data analysis technique was carried out descriptively. The data analysis was carried out by classifying the data, categorizing the data and finding important issues related to the form of absolute poverty. The results showed that in the novel La Muli by Nunuk Y Kusmiana, there are several forms of absolute poverty, namely First, the main character La Muli experiences absolute poverty, namely by not meeting proper food needs. Second, the La Muli figures and local residents do not have private bathrooms and prefer to use the well as a place to bathe and use it for drinking. Third, La Muli who was elected as the head of the RT did not get a salary, but had to spend his personal money to deal with the emergency problems of his citizens. Fourth, La Muli as a fisherman does not have a steady income and cannot buy new sailing equipment to get better catches because of the high price of these tools.